GENERASI Z DI TEMPAT KERJA: MENJEMBATANI WORK-LIFE BALANCE, KECERDASAN EMOSIONAL, DAN PERTUMBUHAN KARYAWAN UNTUK KINERJA OPTIMAL - Saragih, Guntur Syahputra; Supriadi, Yudi Nur; Kinasih, Rada Puspa; Karunia, Meiliza; Puspita, Vannia Salsabila (Gapenas Publisher, 2024)
To maintain or even enhance the current performance of the company, businesses must pay more serious attention to employee performance. Key factors studied include employee development, emotional intelligence, and work-life balance (WLB). This study aims to explore how employee development, emotional intelligence, and WLB affect employee performance through multiple linear regression analysis. The results of hypothesis testing show that WLB, emotional intelligence, and employee development together significantly influence employee performance in the cosmetics industry in Surabaya. However, the influence of WLB on employee performance is relatively smaller compared to other factors studied. Therefore, for the cosmetics industry in Surabaya, there is a need to increase attention to WLB as part of the strategy to help employees achieve a better balance between work and personal life. Thus, improvements in this area can have a positive impact on employee productivity and job satisfaction, and help the company achieve its business goals more effectively amidst the challenges and dynamics of the changing market